Circular RNA circ‐PRKCI functions as a competitive endogenous RNA to regulate AKT3 expression by sponging miR‐3680‐3p in esophageal squamous cell carcinoma. Issue 6 (18th January 2019) - Shi, Naiming; Shan, Ben; Gu, Biao; Song, Yaqi; Chu, Hongjun; Qian, Long
Abstract: Circular RNA (circRNA) is a new noncoding RNAs and plays an important role in many pathological processes. Recently, studies have shown that circular RNA_PRKCI (circ‐PRKCI) regulates cell proliferation and cell migration of tumor cells. Esophageal carcinoma is a highly malignant digestive tract tumor, which is divided into esophageal adenocarcinoma and esophageal squamous cell carcinoma. In this study, we studied whether circ‐PRKCI might influence cell proliferation and cell migration in esophageal squamous cell carcinoma. Quantitative reverse transcription PCR was performed to detect the relative expression of circ‐PRKCI in five cases of esophageal squamous cell carcinoma and five cases of paired adjacent normal tissues. RNA immunoprecipitation assay and Luciferase assay confirm the direct interaction between miR‐3680‐3p and AKT3 or circ‐PRKCI. Ethynyldeoxyuridine assays and cell counting Kit‐8 were performed to evaluate the effect of miR‐3680‐3p or circ‐PRKCI on cell proliferation, transwell assays were also performed to detect migration in vitro. We found circ‐PRKCI is obviously upregulated in esophageal squamous cell carcinoma and upregulation of circ‐PRKCI stimulated cell migration and proliferation of ESCC cells. In the mechanism, we confirm that circ‐PRKCI, as a molecular sponge of miR‐3680‐3p, upregulates the expression of AKT. In conclusion, our current studies have been revealing that circ‐PRKCI/miR‐3680‐3p/AKT3 regulatory network plays an important role in esophageal squamous cell carcinoma and that provide new insights into the pathogenesis of esophageal squamous cell carcinoma. Abstract : We studied the regulation of circular RNA_PRKCI (circ‐PRKCI) on cell proliferation and migration in esophageal squamous cell cancer (ESCC), and confirmed that circ‐PRKCI functions as a competitive endogenous RNA to regulate AKT3 expression by sponging miR‐3680‐3p in esophageal squamous carcinoma. In addition, it may provide us with a new perspective on the diagnosis and treatment of ESCC.